(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Metanephric adenoma is a rare benign renal epithelial tumor, accounting for less than 1% of renal epithelial neoplasms in adults. Despite its benign biological behavior, MA is frequently misdiagnosed as renal cell carcinoma because of its nonspecific clinical presentation and overlapping imaging features. Case presentation: We report a case of a 28-year-old woman who presented with a 5.2 cm right renal mass detected on computed tomography, with imaging features raising suspicion for papillary renal cell carcinoma. The patient underwent radical right nephrectomy. Histopathological examination revealed a tumor composed of relatively uniform small cells arranged in tightly packed small tubules, microcystic structures, and glomeruloid bodies. Immunohistochemistry demonstrated positivity for WT1, BRAF V600E, and Vimentin, with negativity for CK7 and ALK, findings consistent with a diagnosis of metanephric adenoma. Conclusion: Metanephric adenoma remains a diagnostic challenge due to its non-specific clinical and radiological presentation. Definitive diagnosis relies on characteristic histomorphology combined with immunohistochemical profiling, particularly the WT1(+)/BRAF(+)/CK7(-) phenotype. Accurate recognition of metanephric adenoma is essential to prevent overdiagnosis and avoid unnecessary radical surgery.